Efektifitas Murotal Terapi Terhadap Kemandirian Mengontrol Halusinasi Pendengaran - Zainuddin, Ricky; Hashari, Rahmiyanti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Background: Effectiveness of Murotal Therapy Against Independence Controlling Hallucinations,Introduction: Murotal therapy is a recording of surah Al-Qur'an performed by qori readers of the Qur'an where when someone listens to the verses of the Qur'an it will make someone calm. The recitation of the Qur'anic verses reaching the ears then moving to brain cells and influencing them through these frequency electromagnetic fields produced in these cells will respond to these fields and modify their vibrations changes in these vibrations that can make the brain relax and calm so that it can reduce hallucinations. Methods: The data base used in this literature review was Pubmed and Google Scholar. Results: : There are 1.028.205 articles that have been identified and. From the articles obtained there are 755 articles that meet the inclusion criteria. Â Conclusion: From these results it can be concluded that murotal Al-Qur'an therapy can be used as an alternative to treat patients who experience auditory hallucinations.